Pidana Alternatif Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana dan Kaitannya dengan Tujuan Pemidanaan - Allison Dara Dharmawan; Nadira Karisma Ramadanti (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The enactment of the 2023 Criminal Code shows a change in the direction of punishment in Indonesia. The 2023 Criminal Code emphasises the purpose of punishment on prevention, correction, and restoration of balance, in contrast to the old Criminal Code which was more oriented towards providing deterrent effects. This is proven by the emergence of alternative punishment in the form of supervision punishment and social work punishment. The purpose of this study is to examine whether this alternative punishment is appropriate when viewed from the purpose of punishment and how the implementation of alternative punishment in other countries. This alternative punishment not only provides a more humane and restorative punishment option, but is also expected to overcome the problem of overcapacity of Correctional Institutions (Lapas). In addition, this research discusses the implementation of alternative punishment in other countries, such as the Netherlands and Portugal, which have proven effective in reducing the prison population and recidivism rate. By using normative juridical research method, the author makes the Criminal Code 2023 as the main legal basis to be analysed.